The role of GALNT and EGFR in vascular calcification: Study on pathophysiology and its implications in vascular therapy - Bahar, Mokhamad Aswin; Rohman, Mohammad Saifur (Universitas Brawijaya, 2025)
Vascular calcification is a complex biomineralization process that occurs in arteries, primarily driven by the activity of vascular smooth muscle cells (VSMCs). This process involves the deposition of hydroxyapatite minerals in the arterial walls, particularly within the intima and media layers. Vascular calcification significantly increases the risk of cardiovascular diseases, including myocardial infarction, stroke, and heart failure. Understanding the role of GalNAc-transferase (GALNT) and the epidermal growth factor receptor (EGFR) in vascular calcification has advanced significantly. GALNT is involved in the regulation of glycosylation and affects various biochemical pathways, including insulin signaling and lipid metabolism. Variations in GALNT expression can influence the risk of vascular calcification, highlighting the crucial role of glycosylation in the pathogenesis of vascular calcification. On the other hand, EGFR contributes to vascular calcification by modulating the activity of tissue-nonspecific alkaline phosphatase (TNAP) and the formation of calcifying extracellular vesicles, as well as through the proliferation and migration of VSMCs. A deeper understanding of the roles of GALNT and EGFR provides new insights into the pathophysiological mechanisms of vascular calcification and opens up opportunities for the development of more effective therapies. This review aims to enhance scientific knowledge and provide a foundation for further research and the development of more targeted and personalized therapies in the prevention and treatment of vascular calcification.